Subcutaneous Panniculitis-Like T-Cell Lymphoma in a Patient Receiving Long-Term Panniculitis Treatment: A Case Report - Saime Barut (Shiraz University of Medical Sciences, 2021)
Subcutaneous panniculitis-like t-cell lymphoma (SPTL) is known as a rare type of cutaneous lymphoma characterized with penetration of neoplastic T cells to the subcutaneous tissue. It constituates less than 1% of all non-Hodgkin lymphomas. We described herein a 49-year-old woman with SPTL who presented with redpurple- colored persistent subcutaneous nodules disseminated on trunk and both extremities. The lesions were present for 15 years. She had been diagnosed as panniculitis and her lesions had not regressed with panniculitis treatment. SPTL was diagnosed due to histopathological examination of the lesions that revealed CD3 positive, CD8 positive, CD4 negative and CD56 negative atypical lymphoid infiltration with lobular and septal panniculitis-like pattern. SPTL must be always kept in mind as a differential diagnosis, while examining biopsies of patients with panniculitis-like lesions resistant to long-term treatment. It is also important to remember that the biopsy material should be in such depth that involves subcutaneous fat tissue.